41.2k views
2 votes
Three students used factoring to solve a quadratic equation.

Jordan's Solution Keith's Solution Randall's Solution









The equation was solved correctly by . The solutions of the equation are .

Three students used factoring to solve a quadratic equation. Jordan's Solution Keith-example-1
Three students used factoring to solve a quadratic equation. Jordan's Solution Keith-example-1
Three students used factoring to solve a quadratic equation. Jordan's Solution Keith-example-2
Three students used factoring to solve a quadratic equation. Jordan's Solution Keith-example-3

2 Answers

4 votes

Answer:

The first box is Keith and the second box is -5,-12

Explanation:

Three students used factoring to solve a quadratic equation. Jordan's Solution Keith-example-1
User Masteroleary
by
5.7k points
2 votes

Answer:

The solution was solved correctly by Keith

The solutions of the equation are x=-5,x=-12

Explanation:

we have


x^(2)+17x+72=12

Group terms that contain the same variable, and move the constant to the opposite side of the equation


x^(2)+17x=12-72


x^(2)+17x=-60

Complete the square. Remember to balance the equation by adding the same constants to each side.


x^(2)+17x+8.5^(2) =-60+8.5^(2)


x^(2)+17x+72.25 =12.25

Rewrite as perfect squares


(x+8.5)^(2)=12.25

square root both sides


(x+8.5)=(+/-)3.5


x=-8.5(+/-)3.5


x=-8.5(+)3.5=-5


x=-8.5(-)3.5=-12

The solution was solved correctly by Keith

The solutions of the equation are x=-5,x=-12

User Cloud Artisans
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.